2011
DOI: 10.5194/acp-11-2603-2011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ambient aerosol extinction coefficients obtained from in-situ, MAX-DOAS and LIDAR measurements at Cabauw

Abstract: Abstract. In the field, aerosol in-situ measurements are often performed under dry conditions (relative humidity RH<30-40%). Since ambient aerosol particles experience hygroscopic growth at enhanced RH, their microphysical and optical properties -especially the aerosol light scatteringare also strongly dependent on RH. The knowledge of this RH effect is of crucial importance for climate forcing calculations or for the comparison of remote sensing with insitu measurements. Here, we will present results from a f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
136
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(148 citation statements)
references
References 68 publications
(84 reference statements)
10
136
2
Order By: Relevance
“…These systems have been shown to be robust, with high vertical and temporal resolutions that allow for study of the aerosol hygroscopic growth under unmodified ambient conditions. Recent studies presented by Zieger et al (2011) and Rosati et al (2016) show good agreement between in situ and RL extinction coefficients after taking into account the RH effect on the in situ measured extinction coefficient. Also, it is possible to use aerosol extinction coefficient to compare with in situ airborne measures and elastic lidar to study hygroscopic growth in unmodified ambient conditions.…”
Section: Introductionmentioning
confidence: 97%
“…These systems have been shown to be robust, with high vertical and temporal resolutions that allow for study of the aerosol hygroscopic growth under unmodified ambient conditions. Recent studies presented by Zieger et al (2011) and Rosati et al (2016) show good agreement between in situ and RL extinction coefficients after taking into account the RH effect on the in situ measured extinction coefficient. Also, it is possible to use aerosol extinction coefficient to compare with in situ airborne measures and elastic lidar to study hygroscopic growth in unmodified ambient conditions.…”
Section: Introductionmentioning
confidence: 97%
“…The influence of the relative humidity on the aerosol optical properties was e.g. discussed by Zieger et al (2011). Theoretical model studies (Ackermann, 1998) revealed that low relative humidity leads to lower values of the lidar ratio of pollution aerosols.…”
Section: Vertical Layeringmentioning
confidence: 99%
“…The wavelength dependence of scattering enhancement factor f (RH,λ) varies with generalized aerosol types. Kotchenruther and Hobbs (1998) and Zieger et al (2010Zieger et al ( , 2011 found no pronounced wavelength dependence of f (RH,λ) for biomass burning aerosols and arctic aerosols, respectively; Zieger et al (2013) found small variations (< 5 %) of f (RH,λ) at 450, 550, and 700 nm for several European sites; Kotchenruther et al (1999) and Magi and Hobbs (2003) reported significant wavelength dependence of f (RH,λ) for urban/industrial aerosols off the east coast of the United States. In this study, the wavelength dependence of enhancement factors was also investigated.…”
Section: Introductionmentioning
confidence: 99%